Diastereoselective synthesis of functionalized tetrahydropyridazines containing indole scaffolds via an inverse-electron-demand aza-Diels–Alder reaction. Issue 16 (18th June 2021) - Chen, Taotao; Che, Chao; Guo, Zhefei; Dong, Xiu-Qin; Wang, Chun-Jiang
Abstract : A base-promoted and catalyst-free unprecedented inverse-electron-demand aza-Diels–Alder reaction between the in situ generated azoalkenes and 3-vinylindoles has been developed to afford tetrahydropyridazines containing indole scaffolds. Abstract : An unprecedented base-promoted and catalyst-free inverse-electron-demand aza-Diels–Alder (IEDDA) reaction between easily available in situ generated azoalkenes and 3-vinylindoles has been developed. This efficient protocol afforded structurally important tetrahydropyridazines containing indole scaffolds with excellent results (72%–89% yields, >20 : 1 dr). Moreover, the catalytic asymmetric version of this reaction was preliminarily realized through a Cu/( S, S )- i Pr-box system to prepare the desired chiral product with 81% yield and >20 : 1 dr and 93% ee. The cyclization products could also be well functionalized to access other useful organic molecules through simple transformations.